Influence of paclobutrazol on bud growth and yield of Psidum guajava L. in high density - Padilla Ramírez, José Saúl; Rodríguez Moreno, íctor Manuel; González Gaona, rnesto; Osuna Ceja, Esteban Salvador; Pérez Barrazarraza, María Hilda (Revista Mexicana de Ciencias Agrícolas, 2017)
Application of bioregulators is a common practice in several temperate and tropical and subtropical crop fruits to: control vegetative growth, stimulate flowering and fruit set. Paclobutrazol “PBZ” is among those products; however there is few information of its response in guava. Therefore, it was evaluated the application of PBZ on the annual sprout growth dynamic and on the fruit yield of eight guava genotypes established in a high planting density (5 000 plants ha-1 ). The study was carried out at the Experimental Site of “Los Cañones”, during two production cycles. The PBZ treatments were: 0, 1 and 2 ml tree-1 in 2013 and 0 and 1 ml tree-1 in 2015, using the commercial product Austar ® (Paclobutrazol 25%) in both years. The PBZ was applied to the soil around the base of the trunk at the beginning of each cycle, after the pruning. The sprout growth dynamic was measured during 15 weeks after de PBZ was applied in five randomly selected sprouts in one plant of the eight guava genotypes. Daily growth rate (DGR) between each two dates of the sprout growth was estimated. Internodal distance of the same five selected sprouts to measure growth dynamics was registered. At harvest, it was registered: fruit yield, fruit number and the average weight of fruits. The PBZ decreased sprout growth and the internodal distance from 15 to 41%, which was reflected on a lower DGR, being of 4.5 to 6 mm day -1 in the untreated plants, while in the PBZ treated plants DGR was only from 2.8 to 3.9 mm day-1 . In 2013, PBZ significantly increased fruit yield and fruits per plant as compared to the control; however, in 2015 the PBZ did not surpass the control. The outstanding guava genotypes in both years were: Calvillo S-XXI, Selection-12 and Selection-45 with an average of 20.6 kg tree-1 .
Keywords: Psidum guajava , PBZ, growth regulators; sprout length, fruit quality